Deep Cavitand Calixarene–Solubilized Fullerene as a Potential Photodynamic Agent - Zhang, Tian-Xing; Li, Juan-Juan; Li, Hua-Bin; Guo, Dong-Sheng (Frontiers in Chemistry, 2021)
Fullerene has attracted much attention in biomedical research due to its unique physical and chemical properties. However, the hydrophobic nature of fullerene is limited to deploy in the body given that the biofluids are mainly water. In this study, a water-soluble supramolecular nanoformulation based on a deep cavitand calixarene (SAC4A) and fullerene is developed to overcome the hydrophobicity of fullerene and is used as a potential photodynamic agent. SAC4A solubilizes fullerene very well with a simple grinding method. The significantly increased water solubility of fullerene enables efficient activation of reactive oxygen species. The host-guest strategy to solubilize fullerene can not only provide a new method to achieve water solubility, but also expand the biomedical applications of fullerene.